Percutaneous closure of the coronary artery-pulmonary artery fistula in a patient with apical hypertrophic cardiomyopathy - Murat Sünbül; Nurdan Papila Topal; Tarık Kıvrak; Bülent Mutlu (KARE Publishing, 2013)
A fifty-four-year-old female patient was admitted to our unit with exertional chest pain of six months duration. Transthoracic echocardiography showed apical hypertrophy. Upon further investigation, cardiac magnetic resonance imaging revealed apical hypertrophic cardiomyopathy. The patient underwent myocardial perfusion scintigraphy which showed anterior ischemia. Coronary angiography revealed an arteriovenous fistula (AVF) from the left anterior descending artery to the pulmonary artery. The patient's chest pain was attributed to a coronary steal syndrome secondary to the coronary AVF. The AVF fistula was closed with a coil and the patient's chest pain improved. In conclusion, coronary steal syndrome may lead to myocardial ischemia in patients with a coronary AVF.